TRADISI MACOPAT (MAMACA) DALAM MEMPERINGATI HAUL BHUJU’ SOROT DI DESA APAAN PANGARENGAN - Tammamatun Tammamatun; Silvi Putri Labiba (Jurnal Cendekia Pendidikan, 2025)
The Macopat (mamaca) tradition is a form of Madurese oral literature that combines the recitation of poetic texts and stories through song (thembang) and interpretation (tegghes) in the Madurese language. This tradition is not only aesthetically valuable, but also contains high moral and religious values. However, the phenomenon of modernization has caused this tradition to begin to be abandoned and is only preserved in the Haul Bhuju' Sorot event, which is now the only space for the preservation of this culture. This study aims to describe the form of implementation, cultural values, and efforts to preserve the Macopat tradition in Apaan Pangarengan Village. The study uses a descriptive qualitative approach with observation, interview, recording, and data collection techniques as suggested by Esten (in Sudikan, 2014). The results of the study show that (1) the Macopat tradition has disappeared in most traditional events except for Haul Bhuju' Sorot; (2) the preservation of traditions is dominated by the older generation, such as Pak Dulmukit, who has been a pamaos for 25 years; and (3) regeneration is hampered by the lack of interest from the younger generation and the lack of socio-cultural support. These findings emphasize the urgency of preserving Macopat (emergency) through revitalization based on local cultural education (solution) to maintain the sustainability of the religious and moral values of the Madurese people.